Proceedings of the 25th Australian Computer-Human Interaction Conference: Augmentation, Application, Innovation, Collaboration 2013
DOI: 10.1145/2541016.2541072
|View full text |Cite
|
Sign up to set email alerts
|

The Leap Motion controller

Abstract: This paper presents an early exploration of the suitability of the Leap Motion controller for Australian Sign Language (Auslan) recognition. Testing showed that the controller is able to provide accurate tracking of hands and fingers, and to track movement. This detection loses accuracy when the hand moves into a position that obstructs the controller's ability to view, such as when the hand rotates and is perpendicular to the controller. The detection also fails when individual elements of the hands are broug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(21 citation statements)
references
References 3 publications
1
15
0
1
Order By: Relevance
“…Perdana (2014) used Leap Motion to develop an alternative method for teaching children music and performance, concluding that there isn't an ideal motion recognition music based application, and criticising Leap Motion's low range and lack of accuracy (Potter, Araullo, & Carter 2013).…”
Section: Motion Based Devicesmentioning
confidence: 99%
“…Perdana (2014) used Leap Motion to develop an alternative method for teaching children music and performance, concluding that there isn't an ideal motion recognition music based application, and criticising Leap Motion's low range and lack of accuracy (Potter, Araullo, & Carter 2013).…”
Section: Motion Based Devicesmentioning
confidence: 99%
“…In [12], the authors estimated the accuracy and repeatability of hand position measurement and found that this sensor outperforms competitive solutions with a similar price range. In [13], the sensor's usefulness for recognizing Australian Sign Language was assessed. Hand shapes for which the sensor does not work were identified.…”
Section: Related Workmentioning
confidence: 99%
“…It is expected that sensors for the acquisition of hands skeletal data will be improved soon. Therefore, work is underway to use them to recognize sign languages: American [15][16][17][18][19][20][21][22][23][24], Arabic [25][26][27][28], Australian [13], Indian [29][30][31], Mexican [32], Pakistani [33], and Polish [34].…”
Section: Related Workmentioning
confidence: 99%
“…Leigh Ellen Potter will discuss user experience when interacting with emerging technology. These technologies often enable new interaction mechanisms through the use of innovative device capabilities [8]. Established interaction mechanisms may not work effectively with these emerging technologies, affecting the user experience.…”
Section: Overview Of Presentationsmentioning
confidence: 99%